Socio-demographic segmentation in sanitation based engagement in Koja, Jakarta - Aji, Angga Dheta Shirajjudin; Septiariva, Iva Yenis; Nastiti, Almira Davina; Sofiyah, Evi Siti; Ridhosari, Betanti; Suryawan, I Wayan Koko; Suhardono, Sapta; Prayogo, Wisnu (International Journal of Public Health Science (IJPHS), 2025)
Urban public health initiatives rely heavily on community participation to ensure success and sustainability. This study explores the socio-demographic determinants of community engagement in the public health initiatives of Koja Subdistrict, Jakarta. A cross-sectional survey was conducted, employing both qualitative interviews and quantitative questionnaires to gather data from a representative sample. Binary logistic regression was used to analyze the data, focusing on aesthetics, public health sanitation performance, community socialization, gender, age, and education. The findings reveal that aesthetic considerations, perceived sanitation performance, socialization practices, and demographic factors significantly influence the willingness to participate. Aesthetics and community socialization positively impacted engagement, while perceived high sanitation performance paradoxically discouraged individual participation. Furthermore, demographic factors such as gender, age, and education level showed varying degrees of influence, with gender disparities and higher education correlating with increased engagement. This study contributes to understanding public health participation dynamics and offers insight into designing tailored community engagement strategies. Policymakers and health officials can leverage these insights to effectively enhance community involvement and address public health challenges.